De Morgan with quantifiers

De Morgan

val x P : Q x P : Q not for all = at least for one not val x P : Q x P : Q not exists = for all not

Hence: and

It holds further that:

x x x

x x x holds also for quantified formulas! Substitution meta rule

Simple Sequential

Simultaneous EVERY occurrence of P is substituted! holds also for quantified formulas! The rule of Leibniz

meta rule Leibniz

formula that has single occurrence is replaced! as a sub formula Other equivalences with quantifiers

Exchange trick No wonder as

Term splitting Other equivalences with quantifiers Monotonicity of quantifiers

tautologies Lemma E1: iff is a . still hold (in Lemma W4: iff is a tautology. predicate logic)

Lemma W5: If then . Derivations / Reasoning Limitations of proofs by calculation

Proofs by calculation are formal and well-structured, but often undirected and not particularly intuitive. Example

val P ∧ (P∨Q) = (P∨F) ∧(P∨Q) val = P∨(F ∧Q) val we can prove this = P ∨ F if y is not free in P andmore Q intuitively by val = P reasoning

Conclusions P ∧ (P∨Q) =val P P ∧ (P∨Q) ⇔ P =val T An example of a mathematical proof

Theorem If x2 is even, then x is even (x ∊ Z). (sub)goal

Proof Let x∊ Z be such that x2 is even. generating hypothesis We need to prove that x is even too. pure hypothesis Assume that x is odd, towards a contradiction. conclusion If x is odd than x = 2y+1if fory is some not y free∊ Z. in P and Q Then x2 = (2y+1)2 = 4y2 + 4y + 1 = 2(2y2 + 2y) + 1 and 2y2 + 2y ∊ Z.

So, x2 is odd too, and we have a contradiction.

Thanks to Bas Luttik Exposing logical structure

(sub)goal If x2 is even, then x is even (x ∊ Z). generating hypothesis Proof Let x∊ Z Assume x2 is even. pure hypothesis Assume that x is odd. conclusion Then x = 2y+1 for some y ∊ Z. Then x2 = if(2y+1) y is 2not = 4y 2free + 4y +in 1 P= and Q 2(2y2 + 2y) + 1 and 2y2 + 2y ∊ Z.

So, x2 is odd

a contradiction. So, x is even Thanks to Bas Luttik Single rule

Q is a correct conclusion from n premises P1, .. , P n iff val (P1∧ P2 ∧…∧ Pn) ⊨ Q

val If n=0, then P1 ∧ P2 ∧… ∧ Pn = T val Note that T ⊨ Q means that Q = T Q holds unconditionally Derivation

a based on the single Q is a correct conclusion from n premises P1, .. , P n inference rule iff val for proofs that closely (P1∧ P2 ∧…∧ Pn) ⊨ Q follow our intuitive reasoning

Two types of inference rules: for drawing (particularly useful) elimination rules conclusions out of instances of the single premises inference rule introduction rules and one new for simplifying goals special rule!

How do we use a conjunction in a proof? P∧Q ⊨val P

val ∧-elimination P∧Q ⊨ Q

|| || || ||

(k) P∧Q (k) P∧Q

|| || || ||

{∧-elim on (k)} {∧-elim on (k)} (m) P (m) Q

(k < m) (k < m) Implication elimination

How do we use an implication in a proof? P⇒Q ⊨val ???

⇒-elimination ⇒ val || || (P Q) ∧ P ⊨ Q

(k) P⇒Q || ||

(l) P

|| || {⇒-elim on (k) and (l)} (m) Q (k < m, l < m) Conjunction introduction

How do we prove a conjunction? val P∧Q ⊨ P∧Q ∧-introduction …

(k) P …

(l) Q

… {∧-intro on (k) and (l)} (m) P∧Q

(k < m, l < m) Implication introduction

truly new How do we prove an implication? and necessary for reasoning with ⇒-introduction hypothesis … {Assume} (k) P flag shows the of a … hypothesis

(l-1) Q {⇒-intro on (k) and (l-1)} (l) P⇒Q time for an example!

How do we prove a negation? val ¬ P = P ⇒ F

¬-introduction … {Assume} (k) P

… ⇒-intro (l-1) F {¬-intro on (k) and (l-1)} (l) ¬P Negation elimination

How do we use a negation in a proof? P ∧ ¬P ⊨val F ¬-elimination || ||

(k) P || ||

(l) ¬P

|| || {¬-elim on (k) and (l)} time for an (m) F example!

(k < m, l < m) F introduction

How do we prove F? P ∧ ¬P ⊨val F F-introduction …

(k) P … the same as ¬-elim (l) ¬P only intended bottom-up

… {F-intro on (k) and (l)} (m) F

(k < m, l < m) F elimination

How do we use F in a proof? it’s very useful!

val F-elimination F ⊨ P

|| ||

(k) F

|| ||

{F-elim on (k)} (m) P

(k < m) Double negation introduction

How do we prove ¬¬? P ⊨val ¬¬P ¬¬-introduction

(k) P … {¬¬-intro on (k)} (m) ¬¬P

(k < m) Double negation elimination

How do we use ¬¬ in a proof? ¬¬P ⊨val P ¬¬-elimination

|| ||

(k) ¬¬P

|| ||

{¬¬-elim on (k)} (m) P

(k < m) Proof by contradiction

(sub)goal Theorem If x2 is even, then x is even (x ∊ Z). generating hypothesis Proof Let x∊ Z Assume x2 is even. pure hypothesis Assume that x is odd. conclusion Then x = 2y+1 for some y ∊ Z. Then x2 = if(2y+1) y is 2not = 4y 2free + 4y +in 1 P= and Q 2(2y2 + 2y) + 1 and 2y2 + 2y ∊ Z.

So, x2 is odd

a contradiction. So, x is even Thanks to Bas Luttik Proof by contradiction

How do we prove P by a contradiction? ¬P ⇒ F ⊨val ¬¬P ⊨val P proof by contradiction {Assume} (k) ¬P

… ¬-intro (l-1) F {¬-intro on (k) and (l-1)} ¬¬-elim (l) ¬¬P {¬¬-elim on (l)} (l+1) P time for an example! (k < m)